Distinct Roles of Perilipins in the Intramuscular Deposition of Lipids in Glutamine-Supplemented, Low-, and Normal-Birth-Weight Piglets - Zhao, Yaolu; Albrecht, Elke; Li, Zeyang; Schregel, Johannes; Sciascia, Quentin L.; Metges, Cornelia C.; Maak, Steffen (Frontiers in Veterinary Science, 2021)
Piglets with low birth weight (LBW) usually have reduced muscle mass and increased lipid deposition compared with their normal birth weight (NBW) littermates. Supplementation of piglets with amino acids during the first days of life may improve muscle growth and simultaneously alter the intramuscular lipid deposition. The aim of the current study was to investigate the influence of glutamine (Gln) supplementation during the early suckling period on lipid deposition in the longissimus muscle (MLD) and the role of different perilipin (PLIN) family members in this process. Four groups were generated consisting of 72 male LBW piglets and 72 NBW littermates. Piglets were supplemented with either 1 g Gln/kg body weight or an isonitrogenous amount of alanine (Ala) between post-natal day (dpn) 1 and 12. Twelve piglets per group were slaughtered at 5, 12 and 26 dpn and muscle tissue was collected. Perilipins were localized by immunohistochemistry in muscle sections. The mRNA and protein abundances of PLINs and related lipases were quantified by qPCR and western blots, respectively. While PLIN1 was localized around lipid droplets in mature and developing adipocytes, PLIN2 was localized at intramyocellular lipid droplets, PLIN3 and 4 at cell membranes of muscle fibers and adipocytes, and PLIN5 in cytoplasm of undefined cells. The western blot results indicated higher protein abundances of PLIN2, 3, 4 and 5 in LBW piglets (p < 0.05) at 5 dpn compared with their NBW littermates independent of supplementation, while not directly reflecting the mRNA expression. The mRNA abundance of PLIN2 was lower while PLIN4 was higher in piglets at 26 dpn than in piglets at 5 dpn (p < 0.01). Relative mRNA expression of LPL and CGI-58 was lowest in piglets at 5 dpn (p < 0.001). However, ATGL mRNA was not influenced by birth weight or supplementation, but the Spearman correlation coefficients revealed close correlations with PLIN2, 4, 5 mRNA at 5 and 26 dpn (r > 0.5, p < 0.001). The results indicated importance of birth weight and age for intramuscular lipid deposition and different roles of PLIN family members in this process, but no clear modulating effect of Gln supplementation.